Growing up with perinatal HIV: changes in clinical outcomes before and after transfer to adult care in the UK. (16th May 2017) - Judd, Ali; Collins, Intira Jeannie; Parrott, Francesca; Hill, Teresa; Jose, Sophie; Ford, Deborah; Asad, Hibo; Gibb, Diana M.; Sabin, Caroline; ,
Abstract: Introduction : With improved survival, adolescents with perinatal HIV (PHIV) are transitioning from paediatric to adult care, but there are few published data on clinical outcomes post‐transfer. Using linked data from patients in the national UK/Ireland paediatric cohort (CHIPS) and an adult UK cohort of outpatient clinics (UK CHIC), we describe mortality and changes in immunological status post‐transfer. Methods : Participants in CHIPS aged ≥13 years by the end of 2013 were linked to the UK CHIC database. Mixed effects models explored changes in CD4 count before and after transfer, including interactions between time and variables where interaction p < 0.05. Results : Of 1, 215 paediatric participants aged ≥13 years, 271 (22%) had linked data in UK CHIC. One hundred and forty‐six (53%) were female, median age at last visit in paediatric care was 17 [interquartile range, IQR 16, 18] years, median duration in paediatric care was 11.8 [6.6, 15.5] years, and in adult care was 2.9 [1.5, 5.9] years. At last visit in paediatric care, 74% ( n = 200) were on ART, increasing to 84% ( n = 228, p = 0.001) at last visit in adult care. In the 12 months before leaving paediatric care, 92 (47%) had two consecutive viral loads >400 copies/mL or one viral load >10, 000 copies/mL, and likewise 102 (52%) in the 12 months post‐transfer ( p = 0.79). Seven (3%) people died in adult care. In multivariable analysis, CD4 declined as patients approached transition with a greater decline in those with higher nadir CD4 count (mean rates of decline of 3, 13, 15, 30 cells/mm 3 per year for those with nadir CD4 < 100, 100–199, 200–299 and ≥300 cells/mm 3, respectively). Post‐transition, CD4 continued to decline in some groups (e.g. black males, −20 (−34, −5) cells/mm 3 per year post transition, p = 0.007)) while it improved in others. Overall CD4 was higher with later year of birth (14 (7, 21) cells/mm 3 per later year). There was no effect of age at transfer or changing hospital at transfer on CD4. Conclusions : Our findings suggest that CD4 in adolescents with perinatal HIV in the UK was declining in the period before transition to adult care, and there was some reversal in this trend post‐transfer in some groups. Across the transition period, CD4 was higher in those with later birth years, suggesting improvements in clinical care and/or transition planning over time.